2023
DOI: 10.4103/1673-5374.390971
|View full text |Cite
|
Sign up to set email alerts
|

Brain dysfunctions and neurotoxicity induced by psychostimulants in experimental models and humans: an overview of recent findings

Marcello Serra,
Nicola Simola,
Alexia E. Pollack
et al.

Abstract: Preclinical and clinical studies indicate that psychostimulants, in addition to having abuse potential, may elicit brain dysfunctions and/or neurotoxic effects. Central toxicity induced by psychostimulants may pose serious health risks since the recreational use of these substances is on the rise among young people and adults. The present review provides an overview of recent research, conducted between 2018 and 2023, focusing on brain dysfunctions and neurotoxic effects elicited in experimental models and hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 207 publications
0
1
0
Order By: Relevance
“…Alongside cocaine, amphetamine (AMPH) and its derivatives including 3,4-methylenedioxymethamphetamine (MDMA) are widely recognized as some of the most misused psychostimulants, especially among adolescents. These substances trigger an excessive release of monoamines at the synaptic level by binding membrane-located transporters of dopamine [ 61 ], norepinephrine, and serotonin [ 62 ] but also lead to a sustained rise in glutamate, leading to neurotoxicity [ 63 ]. Studies on rats showed that repeated exposure to methamphetamine augmented glutamate levels within various brain regions including the striatum [ 64 ], hippocampus [ 65 ], VTA [ 66 ], nucleus accumbens, and PFC [ 67 ].…”
Section: Involvement Of Glutamate Excitotoxicity In Substance Use Dis...mentioning
confidence: 99%
“…Alongside cocaine, amphetamine (AMPH) and its derivatives including 3,4-methylenedioxymethamphetamine (MDMA) are widely recognized as some of the most misused psychostimulants, especially among adolescents. These substances trigger an excessive release of monoamines at the synaptic level by binding membrane-located transporters of dopamine [ 61 ], norepinephrine, and serotonin [ 62 ] but also lead to a sustained rise in glutamate, leading to neurotoxicity [ 63 ]. Studies on rats showed that repeated exposure to methamphetamine augmented glutamate levels within various brain regions including the striatum [ 64 ], hippocampus [ 65 ], VTA [ 66 ], nucleus accumbens, and PFC [ 67 ].…”
Section: Involvement Of Glutamate Excitotoxicity In Substance Use Dis...mentioning
confidence: 99%